Enhanced hydrogen sensitivity of AlGaN/GaN heterojunction gas sensors by GaN‐cap layer. Issue 14 (1st July 2018) - Chung, G.; Cha, H.‐Y.; Kim, H.
Abstract : We fabricated Pt‐functionalised hydrogen gas sensors on AlGaN/GaN heterojunction platform and investigated the influence of GaN‐cap layer on the sensing characteristics. Pt‐Schottky diodes with GaN‐cap layer exhibited a larger change of Schottky barrier height than ones with no GaN‐cap layer when hydrogen gas was detected. Technology computer‐aided design simulation indicated that the increase of electron concentration at heterojunction can be magnified by a larger change of barrier height. The AlGaN/GaN FET‐type sensors with Pt catalyst on the gate area demonstrated significant enhancement of hydrogen gas sensitivity from 16 to 35% at 200°C when GaN cap layer was employed.